Bergenin Activates SIRT1 as a Novel Therapeutic Agent for Osteogenesis of Bone Mesenchymal Stem Cells - Hou, Weiduo; Ye, Chenyi; Chen, Mo; Li, Weixu; Gao, Xiang; He, Rongxin; Zheng, Qiang; Zhang, Wei (Frontiers in Pharmacology, 2019)
Bone mesenchymal stem cells (BMSCs) are important candidates for bone regeneration. The role of Bergenin, a C-glucoside of 4-O-methyl gallic acid obtained from the species, Bergenia, in BMSC osteogenesis has not yet been elucidated. We therefore investigated the effects of Bergenin on the osteogenesis of BMSCs and found that Bergenin enhanced osteoblast-specific markers and downregulated the adipocyte-specific markers in vitro. Furthermore, using a rat calvarial defect model, we found that Bergenin significantly improved bone healing, as determined by imaging and histological analyses. Moreover, it also upregulated SIRT1 expression. A SIRT1 inhibitor (EX 527) decreased the enhanced bone mineral formation caused by Bergenin. Taken together, these findings show that Bergenin accelerated the osteogenic differentiation of BMSCs, at least partly through the activation of SIRT1.